Upgrade your knowledge in tax: Tax awareness from an early age in education - Lady Karlinah; Wahono Diphayana; Ni Komang Candra Wiguna (University of Merdeka Malang, 2024)
Taxes are the main pillar of government development funding, as mandated by Indonesian law. The primary challenge at Erenos High School in South Tangerang is the lack of taxpayer awareness regarding tax compliance. There is an urgent need to change citizens' perspectives on fiscal education from an early age through systematic strategies, including curriculum and student activities. The education sector has welcomed the Directorate General of Taxes' initiative to include tax education in the curriculum, fostering tax awareness among the younger generation. The implementation process includes several phases: interviews and discussions, module preparation, presentations, training and discussions, and mentoring. The Community Service Team monitored the activities, observing significant student interest in the subject matter presented. The students' enthusiasm and high participation indicated strong curiosity, evidenced by the variety of questions directed at the speakers. The speakers' engagement in asking about the students' tax knowledge was clear from the final evaluation results, showing that 91.8% of participants felt they had begun to understand their responsibilities as taxpayers. This initiative aims to instill a sense of tax awareness early on, ensuring that future generations are well-informed and compliant with tax regulations, ultimately supporting government development efforts.